Changes in motor and sensory parameters in patients with lumbar disc herniation (Annals of Medical Research, 2023)
Aim: Our main aim is to research whether there is motor and sensory loss between the healthy and the affected part in patients with unilateral L5 root compression. It is also to specify the pain and quality of life of patients.Materials and Methods: Muscle strength were evaluated with a manual dynamometer, Light touch/pressure sense in the L5 dermatome was measured by Semmes Weinstein Monofilament, two-point discrimination sense was discriminated and ankle proprioception sense was measured with a goniometer. Pain severity of the patients was utilized with Visual Analogue Scale and quality of life was evaluated with Short Form-36.Results: A significant difference was found between the affected-unaffected parts of patients with spinal disc herniation in terms of motor and sensory measurements, (p
Keywords: Lumbar disc herniation; Motor impairment; Sensory impairment